Hubungan Perilaku Pemeliharaan Kebersihan dengan Status Gingiva pada Pengguna Gigi Tiruan Sebagian Lepasan - Baba, Puspitasari; Wowor, Vonny N.S.; Tendean, Lydia (Universitas Sam Ratulangi, 2018)
Abstract: Denture hygiene behavior is an important factor in the success of denture treatment because it has a close relationship with attitude, knowledge, and action of denture wearers. Improper maintance of denture hygiene can cause problems to oral health, especially in removable denture wearers. Gingiva is often used as an indicator of periodontal diseases. This study was aimed to obtain the denture hygiene behavior, gingival status, and the relationship between these two conditions among partial removal acrylic-based denture wearers at Wawalintoan, West Tondano. This was a descriptive analytical study with a cross-sectional design performed on 68 respondents wearing partial removal acrylic-based dentures obtained by using purposive sampling technique. Data were collected through questionnaire of denture hygiene behavior and examination of gingival index. The results showed that the respondents had good knowledge, attitude, and action of dental hygiene with an average score of 453 (66.6%). The gingival status was categorized as mild in 39 people (57.4%). The relationship between hygiene maintance and gingival status of the respondents analyzed by using the chi-square test obtained a P-value of 0.000 <0.05. Conclusion: There was a significant relationship between denture hygiene behavior and gingival status of partial removable denture wearers.Keywords: hygiene maintance behavior, gingival status, partial removable dentureÂ Abstrak: Perilaku pemeliharaan kebersihan gigi tiruan merupakan faktor penting dalam keberhasilan perawatan gigi tiruan karena berhubungan erat dengan pengetahuan, sikap, dan tindakan pengguna gigi tiruan. Pemeliharaan kebersihan gigi tiruan yang kurang baik dapat menimbulkan masalah bagi kesehatan gigi dan mulut terutama pada pengguna gigi tiruan lepasan. Gingiva sering dijadikan sebagai indikator pada penyakit jaringan periodontal. Penelitian ini bertujuan untuk mengetahui gambaran perilaku pemeliharaan kebersihan, status kesehatan gingiva pada pemakai gigi tiruan, dan hubungan perilaku pemeliharaan kebersihan dengan status gingiva pada pengguna gigi tiruan sebagian lepasan (GTSL) berbasis akrilik. Jenis penelitian ialah deskriptif analitik dengan desain potong lintang yang dilakukan pada 68 responden pengguna GTSL berbasis akrilik di Kelurahan Wawalintoan, Kecamatan Tondano Barat yang dipilih menggunakan teknik purposive sampling. Pengumpulan data dilakukan melalui kuesioner perilaku pemeliharaan kebersihan dan pemeriksaan indeks gingiva. Hasil penelitian menunjukkan bahwa dari pemeliharaan kebersihan gigi, responden memiliki pengetahuan, sikap, dan tindakan yang tergolong baik dengan skor rerata 453 (66,6%). Status gingiva responden tergolong kategori ringan sebanyak 39 orang (57,4%). Hasil uji chi-square terhadap hubungan antara pemeliharaan kebersihan dan status gingiva pengguna GTSL mendapatkan P=0,000 â‰¤0,05. Simpulan: Terdapat hubungan bermakna antara perilaku pemeliharaan kebersihan dan status gingiva pada pengguna GTSL.Kata kunci: perilaku pemeliharaan kebersihan, status gingiva, GTSL